Analisis Penyelesaian Sengketa dalam Perspektif Hukum Internasional (Studi Kasus Sengketa Perbatasan Wilayah Darat Noel Besi-Citrana dan Bidjael Sunan Oben antara Indonesia dengan Timor Leste) - Juniza Indah Setiawati; Rizky Eka Nur Oktaviyani (CV Rewang Rencang, 2023)
International law is the law that exists in the international world as well as to maintain relations between existing countries. In international law, there are interrelationships of various countries that are international in nature, and there are disputes that occur between countries. International disputes that occur can disrupt relations between disputing countries and in international relations. As is the case with the international dispute that occurred between Indonesia and Timor Leste regarding the land border dispute between the two countries. Settlement of international disputes can be done by peaceful and non-peaceful means. The settlement of disputes peacefully can be in the form of negotiations between the two disputing countries carried out in the realm of international law. This study aims to determine the resolution of international disputes from countries in dispute under international law. The method used is an empirical qualitative method with a historical approach. With the resolution of international disputes carried out by peaceful means, it is hoped that international disputes that occur through negotiations can be resolved by prioritizing the peaceful way. Then to improve the good relations of the disputing countries and to improve the relations of the disputing countries to be better in accordance with existing international law.